The Effect of Product Design, Price Perception, and Promotion on Impulsive Buying Decisions at MR D.I.Y in Palu City - Subakti, I Gede Andre; Zahara, Zakiyah; Rombe, Elimawaty; Islianty, Nur Riski (Universitas Muhammadiyah Pontianak, 2026)
This study aims to examine the effect of product design, price perception, and promotion on consumers’ impulsive buying decisions at MR D.I.Y in Palu City. The background of this study is based on the increasing trend of unplanned (impulsive) purchases, which are driven by marketing strategies such as attractive product packaging, aggressive promotional activities, and affordable pricing. This study employs a quantitative approach using a purposive sampling technique, involving 80 respondents who have shopped at MR D.I.Y Palu and are over 18 years of age. Data were collected through questionnaire distribution and analyzed using multiple linear regression analysis.